Coronary artery disease in patients with diabetes type 2 - Janeczko-Sosnowska, Ewa; Sosnowski, Cezary (Przewodnik Lekarza/Guide for GPs, 2005)
Diabetes and prediabetes increase the risk of coronary artery disease. In diabetic patients atherosclerotic changes in coronary arteries are more diffused, advanced and progress faster, with accompanying left ventricular dysfunction. Acute coronary syndrome outcomes are poorer in diabetic subjects compare to non-diabetics. Coronary heart disease treatment in this group should be composed. The more important role in therapy play adequate metabolic control of diabetes, proper blood pressure and lipid metabolism control. It is also necessary to eliminate other atherosclerosis risk factors.